Analysis and applications of nanoparticles in capillary electrophoresis - Ban, Eunmi; Yoo, Young Sook; Song, Eun Joo (ELSEVIER, 2015)
Nanoparticles (NPs) exhibit unique chemical and physical properties that depend on their size, shape, and environment. NPs are emerging as new tools and techniques in the analytical study of various materials and in the biological and biomedical fields, because of their unique properties. Therefore, the quantitative and qualitative characterization of NPs has gathered increasing interest. Additionally, the NPs are being used in rapidly developing techniques to provide highly sensitive and specific analysis of various materials. Capillary electrophoresis (CE) has been demonstrated as a useful analytical tool for the characterization of NPs and for the evaluation of biological and biomedical studies using NPs because of its simple sample preparation and efficient resolution of a diverse size range of compounds. This paper gives a short overview of the analysis and applications of NPs in CE systems, with an emphasis on biological and biomedical studies (C) 2015 Elsevier B.V. All rights reserved.
Keywords: QUANTUM DOTS; MICROCHIP ELECTROPHORESIS; GOLD NANOPARTICLES; SURFACE FUNCTIONALIZATION; GEL-ELECTROPHORESIS; SEPARATION; PARTICLES; ELECTROCHROMATOGRAPHY; BIOCONJUGATION; DNA